2013
DOI: 10.4236/jep.2013.47078
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Contamination in Vegetables at the Farm Gate Due to Irrigation with Wastewater in the Tamale Metropolis of Northern Ghana

Abstract: The rational for this study was to assess the microbial quality of fresh vegetables at the farm gate of the Water Works road vegetable farm at Gumbihini in the Tamale Metropolis. A total of thirty-six (36) vegetables comprising lettuce, amarantus and cabbages and eight (8) wastewater samples were collected at random and analysed for a period of four months, to assess the microbial contamination level. Samples were analysed for total coliforms, faecal coliforms, E. coli and helminthes eggs. All vegetables sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 14 publications
3
13
2
Order By: Relevance
“…High loads of these microfloras were also reported in other studies. Fecal coliforms were found in lettuce at production sites with loads ranging from 10 3 to 10 5 CFU/g and 10 3 to 10 4 CFU/g respectively, in Ghana in the works of Cobbina et al (2013) and Ethiopia those Woldetsadik et al (2017). Mesophilic aerobic germs (3x10 5 to 1.1x10 6 CFU/g) and fungal flora (2x10 3 to 2x10 4 ) were reported in lettuce grown in Romania (Soendjojo, 2012).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…High loads of these microfloras were also reported in other studies. Fecal coliforms were found in lettuce at production sites with loads ranging from 10 3 to 10 5 CFU/g and 10 3 to 10 4 CFU/g respectively, in Ghana in the works of Cobbina et al (2013) and Ethiopia those Woldetsadik et al (2017). Mesophilic aerobic germs (3x10 5 to 1.1x10 6 CFU/g) and fungal flora (2x10 3 to 2x10 4 ) were reported in lettuce grown in Romania (Soendjojo, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Contamination of vegetables is one of the potential risks of infection with enteropathogenic bacteria such as Salmonella and Escherichia coli. This contamination occurs from an environmental, animal or human source at the time of planting, harvesting or handling vegetable prior to consumption (Cobbina et al, 2013;Wognin et al, 2013). Considered as a contamination of plant surfaces, recent work has shown that certain pathogens such as salmonella are able to infect and multiply in the mesophyll of certain plants such as lettuce (Kroupitski et al, 2009;Guchi et al, 2010;Pelletier et al, 2011;Schikora et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The faecal pathogens may cause diseases to farmers, consumers and communities (Abakpa et al, 2013;Cobbina et al, 2013). These studies reported faecal bacterial contamination in vegetables including lettuce and Swiss chards irrigated with LQIW.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, chambers of general use are applied, e.g. Fuchs-Rosenthal (which is also used in cytology, haematology, microbiological and protozoological examinations) [28,29], Sedgwick-Rafter [30,31], or Doncaster chambers -most often used in hydrobiology and sanitary engineering, more rarely in veterinary medicine while counting developmental forms of parasites -mainly the eggs of helminths [32].…”
Section: Basic Division Of Diagnostic Techniquesmentioning
confidence: 99%